2010
DOI: 10.1093/brain/awq129
|View full text |Cite
|
Sign up to set email alerts
|

Connected speech production in three variants of primary progressive aphasia

Abstract: Primary progressive aphasia is a clinical syndrome defined by progressive deficits isolated to speech and/or language, and can be classified into non-fluent, semantic and logopenic variants based on motor speech, linguistic and cognitive features. The connected speech of patients with primary progressive aphasia has often been dichotomized simply as 'fluent' or 'non-fluent', however fluency is a multidimensional construct that encompasses features such as speech rate, phrase length, articulatory agility and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
610
8
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 448 publications
(687 citation statements)
references
References 69 publications
58
610
8
11
Order By: Relevance
“…This finding is not unexpected because, though not always assessed systematically, atrophy of rostral-inferior temporal structures has been consistently reported in svPPA (also known as semantic dementia) both at a group level and individually. 7,10,[30][31][32][33][34][35] Given the uniform pattern of atrophy seen in this consecutively recruited cohort of 21 patients with svPPA, it can be argued that the diagnosis of svPPA should be seriously questioned in the absence of this atrophy pattern. Gil-Navarro et al 36 found the same consistent presence of anterior temporal lobe atrophy in a study of 29 patients with PPA that included 5 with svPPA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is not unexpected because, though not always assessed systematically, atrophy of rostral-inferior temporal structures has been consistently reported in svPPA (also known as semantic dementia) both at a group level and individually. 7,10,[30][31][32][33][34][35] Given the uniform pattern of atrophy seen in this consecutively recruited cohort of 21 patients with svPPA, it can be argued that the diagnosis of svPPA should be seriously questioned in the absence of this atrophy pattern. Gil-Navarro et al 36 found the same consistent presence of anterior temporal lobe atrophy in a study of 29 patients with PPA that included 5 with svPPA.…”
Section: Discussionmentioning
confidence: 98%
“…6 Degeneration of the left frontal operculum and rostral insula is the culprit lesion in nfvPPA. More recent studies have also highlighted involvement of premotor 32 and basal ganglia 37 regions. Like svPPA, the group-average voxel-based morphometry findings in our nfvPPA cohort were largely compatible with the proposed diagnostic recommendations.…”
mentioning
confidence: 97%
“…The nature of WR's language impairment was categorized as that of logopenic PPA (Gorno-Tempini et al, 2011;Wilson et al, 2010). In logopenic PPA cell loss is initially apparent in posterior-superior temporal lobe structures (Wilson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of WR's language impairment was categorized as that of logopenic PPA (Gorno-Tempini et al, 2011;Wilson et al, 2010). In logopenic PPA cell loss is initially apparent in posterior-superior temporal lobe structures (Wilson et al, 2010). The behavioral profile is considered similar to that of vascular conduction aphasia (Gorno-Tempini, Dronkers, Rankin, Ogar, La Phengrasamy, Rosen, … Miller, 2004), although Rohrer, Rossor and Warren (2010) (Howard, Swinburn, & Porter, 2004)).…”
Section: Introductionmentioning
confidence: 99%
“…No discurso dos pacientes com APP-L, Wilson et al (2010) reconheceram as mesmas características dos demais subtipos da APP, porém em menor gravidade. Foram observados erros sintáticos e fonológicos vistos na APP-G, e a dificuldade de acesso lexical que é característica da APP-S.…”
Section: Subtipo Logopênico (App-l)unclassified